One Night on TV Is Worth Weeks at the Paramount : Popular Music on Early Television - Forman, Murray, 1959- (Book collections on Project MUSE., 2012)
Musical performance has been a part of television since the introduction of the medium. The styles and production requirements of music and of television have long influenced the other. Murray Forman gives the history of this interaction, going back to the early years of television, before the broadcast networks, up through the late fifties. He explores the full range of popular music from show tunes to Latin in a wide variety of television programs, and shows how the standards of presentation and performance developed.